If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3 = 5x Reorder the terms: -3 + 12x = 5x Solving -3 + 12x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -3 + 12x + -5x = 5x + -5x Combine like terms: 12x + -5x = 7x -3 + 7x = 5x + -5x Combine like terms: 5x + -5x = 0 -3 + 7x = 0 Add '3' to each side of the equation. -3 + 3 + 7x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = 0 + 3 7x = 0 + 3 Combine like terms: 0 + 3 = 3 7x = 3 Divide each side by '7'. x = 0.4285714286 Simplifying x = 0.4285714286
| 3x+4y=59 | | 0.12+-0.6=-0.06 | | lg(10x^2)lgx=1 | | 9y-47=t+73 | | ln(25x)-ln(x-1)= | | b^2+3=2 | | -4x-7y=-12 | | 3+5+6+9=23 | | n^2=38 | | 15b=1.5 | | n^2-19=-3 | | 5x^2+15x+15=5 | | 32timesn-435=179 | | 3k^2+48k+192=0 | | 9b-2=8 | | 6x-5(2x-1)=5x+17 | | y-120=60(x-2) | | 300=m+100 | | sqrt(x-4)+sqrt(2x-7)=5 | | 2.6666666666666=18 | | 16y-14x=26 | | (3+4)+z=(4+8) | | 5a-9=a+15 | | M+4n-3=0 | | 18+32(2)-(-20)= | | (2x-4)=(2x-6) | | 10=8+24 | | 12p=p+12+p | | (2x-6)=(2x-4) | | 9c-8=4c+12 | | 2x-6=2x-4 | | .40n=10 |